I've seen a way [compact disc] (Fire Talk Records, 2023)
Recorded in caves, crypts, and shopping centers, Mandy, Indiana's debut album is everywhere at once: Their first recordings emerged around 2019, with a smattering of early singles released not long after, culminating in 2021's critically acclaimed '...' EP which saw the band draw early cosigns including a remix from Daniel Avery and support slots from Squid, and Gilla Band. Buried found sound samples, sprawling percussive experiments are arranged via oblique references to film soundtrack strategies and experimental video games.